Coached practice using ERCP mechanical simulator improves trainees’ ERCP performance: a randomized controlled trial - Liao, Wei-Chih; Leung, Joseph W.; Wang, Hsiu-Po; Chang, Wen-Hsinug; Chu, Cheng-Hsin; Lin, Jaw-Town; Wilson, Robert E.; Lim, Brian S.; Leung, Felix W. (Endoscopy, 2013)
Background and study aims: Preliminary data suggested that simulation practice using an endoscopic retrograde cholangiopancreatography (ERCP) mechanical simulator (EMS) improved trainees’ skill. The aims of the current study were to confirm the impact of coached EMS practice at the beginning of ERCP training and to investigate whether subsequent uncoached EMS practice provides additional benefit.Methods: Trainees entering ERCP training in 2008 (n = 8) and 2009 (n = 8) at two referral medical centers were randomized to receive a coached EMS practice either with (2009) or without (2008) subsequent uncoached practices or only routine training (controls). The outcome measures were successful deep biliary cannulation by the trainee and overall performance score as rated by blinded trainers, during the subsequent 3 months of clinical practice.Results: Trainees undergoing single and multiple EMS practices were more likely than controls to achieve successful biliary cannulation (single: adjusted odds ratio [aOR] 2.89, 95 % confidence interval [CI] 2.21 – 3.80 [P < 0.001]; multiple: 3.09, 95 %CI 1.13 – 8.46 [P = 0.028]) and to have superior overall performance scores (aOR 3.29, 95 %CI 1.37 – 7.91 [P = 0.008] and 6.92, 95 %CI 3.77 – 12.69 [P < 0.001], respectively). The benefit of single and multiple EMS practices on overall performance score remained significant after adjustment for success or failure of deep biliary cannulation (aOR 2.98, 95 %CI 1.38 – 6.43 [P = 0.005] and 6.09, 95 %CI 2.40 – 15.45 [P < 0.001], respectively). The benefits of single vs. multiple EMS practices were not statistically different.Conclusions: Coached simulation using EMS improved novice trainees’ success of biliary cannulation and overall ERCP performance. Additional uncoached practices did not appear to provide further benefit. Trainees should undergo a coached EMS practice at the beginning of ERCP training.